Mitigation of the Toxic Effects of Periodontal Pathogens by Candidate Probiotics in Oral Keratinocytes, and in an Invertebrate Model - Moman, Raja; O’Neill, Catherine A.; Ledder, Ruth G.; Cheesapcharoen, Tanaporn; McBain, Andrew J. (Frontiers in Microbiology, 2020)
The larvae of the wax moth Galleria mellonella and human oral keratinocytes were used to investigate the protective activity of the candidate oral probiotics Lactobacillus rhamnosus GG (LHR), Lactobacillus reuteri (LR) and Streptococcus salivarius K-12 (SS) against the periodontal pathogens Fusobacterium nucleatum (FN), Porphyromonas gingivalis (PG) and Aggregatibacter actinomycetemcomitans (AA). Probiotics were delivered to the larvae (i) concomitantly with the pathogen in the same larval pro-leg; (ii) concomitantly with the pathogen in different pro-legs and (iii) before inoculation with the pathogen in different pro-legs. Probiotics were delivered as viable cells, cell lysates or cell supernatants to the oral keratinocytes concomitantly with the pathogen. The periodontal pathogens killed at least 50% of larvae within 24 h although PG and FN were significantly more virulent than AA in the order FN>PG>AA and were also significantly lethal to mammalian cells. The candidate probiotics, however, were not lethal to the larvae or human oral keratinocytes at doses up to 107 cells/larvae. Wax worm survival rates increased up to 60% for some probiotic/pathogen combinations compared with control larvae inoculated with pathogens only. SS was the most effective probiotic against FN challenge and LHR the least, in simultaneous administration and pre-treatment, SS and LR were generally the most protective against all pathogens (up to 60% survival). For P. gingivalis, LR>LHR>SS, and for A. actinomycetemcomitans SS>LHR and LR. Administering the candidate probiotics to human oral keratinocytes significantly decreased the toxic effects of the periodontal pathogens. In summary, the periodontal pathogens were variably lethal to G. mellonella and human oral keratinocytes and the candidate probiotics had measurable protective effects, which were greatest when administrated simultaneously with the periodontal pathogens, suggesting protective effects based on bacterial interaction, and providing a basis for mechanistic studies.